2019
DOI: 10.1111/ejn.14628
|View full text |Cite
|
Sign up to set email alerts
|

Anxious to see you: Neuroendocrine mechanisms of social vigilance and anxiety during adolescence

Abstract: Social vigilance is a behavioral strategy commonly used in adverse or changing social environments. In animals, a combination of avoidance and vigilance allows an individual to evade potentially dangerous confrontations while monitoring the social environment to identify favorable changes. However, prolonged use of this behavioral strategy in humans is associated with increased risk of anxiety disorders, a major burden for human health. Elucidating the mechanisms of social vigilance in animals could provide im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 157 publications
(159 reference statements)
0
20
0
Order By: Relevance
“…Thus, despite having lower resilient functioning, this does not seem to impact friendship quality in adolescent girls. Other factors, such as the emergence of gonadal hormone secretion in adolescence, may underpin higher vulnerability in girls in general (Wright, Hostinar, & Trainor, 2019). Perhaps our findings of equal friendship quality despite lower resilient functioning in girls may, in part, be due to the fact that girls report to have more positive connections with parents, teachers and adults outside the school, higher levels of communication, higher empathy and more help-seeking behaviours when compared to boys (Sun & Stewart, 2007).…”
Section: Discussionmentioning
confidence: 73%
“…Thus, despite having lower resilient functioning, this does not seem to impact friendship quality in adolescent girls. Other factors, such as the emergence of gonadal hormone secretion in adolescence, may underpin higher vulnerability in girls in general (Wright, Hostinar, & Trainor, 2019). Perhaps our findings of equal friendship quality despite lower resilient functioning in girls may, in part, be due to the fact that girls report to have more positive connections with parents, teachers and adults outside the school, higher levels of communication, higher empathy and more help-seeking behaviours when compared to boys (Sun & Stewart, 2007).…”
Section: Discussionmentioning
confidence: 73%
“…11 The neural networks that regulate social vigilance mainly comprise the bed nucleus of the stria terminalis and prefrontal cortex. 12 Patients with anxiety disorders usually show behavioural avoidance, and the avoidance neural network includes the dorsal anterior cingulate cortex, anterior insula, General Psychiatry sublenticular extended amygdala and temporal pole. Notably, the functional connectivity between the amygdala and the anterior insula is associated with the degree of avoidance.…”
Section: Brain Structures Associated With Anxiety Disordersmentioning
confidence: 99%
“…For example, gonadal steroid surges quickly contribute to alterations within the limbic system, and the prefrontal cortex matures gradually, enabling social behavior [42]. Gonadal hormone secretion emerged and affected the structure and function of neural circuits in the prefrontal cortex and stria terminalis across adolescence and may play an important role in anxiety, especially in the gender differences observed during adolescence [43]. Previous evidence showed that the prevalence of depressive symptoms was higher among urban adolescents [44].…”
Section: Sociodemographic Characteristic Of Participantsmentioning
confidence: 99%